2001
DOI: 10.1109/20.951344
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of adherent cell orientation and morphology under strong magnetic fields

Abstract: In the present study, the effect of magnetic fields on the orientation of adherent cells was investigated quantitatively using a long-term magnetic field exposure system at 8 T. Smooth muscle cells, which are classified as adherent cells, were passaged and dispersed in Dulbecco's Modified Eagle's Medium (DMEM). A cell culture flask was filled to capacity with the smooth muscle cell suspension, and placed in the center of a superconducting magnet's bore. The smooth muscle cell culture was incubated for 3 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…Torbet et al [1981] first observed the magnetic orientation of fibrin. We also observed the magnetic orientation of adherent cells such as osteoblasts [Kotani et al, 2000[Kotani et al, , 2002, vascular endothelial cells, smooth muscle cells [Umeno et al, 2001;Umeno and Ueno, 2003;Iwasaka and Ueno, 2003a,b;Iwasaka et al, 2003], human kidney cells , and Schwann cells [Eguchi et al, 2003a;Eguchi and Ueno, 2005] under 8 or 14 T magnetic field exposures.…”
Section: Effects Of Static Magnetic Fields and Magnetic Control On Cementioning
confidence: 83%
See 1 more Smart Citation
“…Torbet et al [1981] first observed the magnetic orientation of fibrin. We also observed the magnetic orientation of adherent cells such as osteoblasts [Kotani et al, 2000[Kotani et al, , 2002, vascular endothelial cells, smooth muscle cells [Umeno et al, 2001;Umeno and Ueno, 2003;Iwasaka and Ueno, 2003a,b;Iwasaka et al, 2003], human kidney cells , and Schwann cells [Eguchi et al, 2003a;Eguchi and Ueno, 2005] under 8 or 14 T magnetic field exposures.…”
Section: Effects Of Static Magnetic Fields and Magnetic Control On Cementioning
confidence: 83%
“…We introduced an orientational order parameter to quantitatively evaluate the degree of orientation of adherent cells exposed to strong static magnetic fields [Umeno et al, 2001;Umeno and Ueno, 2003]. The value of the order parameter was estimated with the Fourier transform of microscopic images.…”
Section: Effects Of Static Magnetic Fields and Magnetic Control On Cementioning
confidence: 99%
“…In our last study, we observed a novel phenomenon in which adherent smooth muscle cells directed their long axis along strong static magnetic fields of 8 T [Umeno et al, 2001]. A possible origin of the observed phenomenon was the diamagnetic anisotropy of smooth muscle cells, which have rodlike shapes, adhering on the substrate.…”
Section: Introductionmentioning
confidence: 94%
“…Higashi et al [4] reported that red blood cells and blood platelets orient along the direction of magnetic flux. The effects of strong magnetic fields on adherent cell alignments with [5] and without [6] magnetically aligned collagen fibers have also been reported.…”
Section: Introductionmentioning
confidence: 99%